PERISTIWA PERANG SEBAGAI SUMBER IDE PENCIPTAAN SENI GRAFIS - Reza Sastra Wijaya; Dharsono Sony Kartika; Febri Yulika (Institut Seni Indonesia Padang Panjang, 2016)
ABSTRACT War is an act of violence involving physical and non-physical action, in other words, it’s a state of hostility between two or more groups of people. The development of human thoughts also has role in the development of weaponry technology. This raises the question of why humans utilize their intelligence and development to invent the destroying and killing instruments. On the contrary, the man himself utterly demands peace.In this creation, war served as a stimulus and observed object that inspired the creation. In order to feel the fright of war, deep exploration of numerous actual sources such as news observations and viewing in-the-middle-of-the-battlefield video were done. From the observation of various objects, certain feelings were obtained and then turned into the subject matter of mental form of creation that’s expressed through the medium of printmaking. The idea of the creation adopted the shape of buffalo’s horn as a result of reinterpretation toward reality. Distortion and visual stylization were later executed to obtain new visualization. Technically, the process of this work adopted conventional graphic arts/printmaking techniques such as relief printing technique (high printing) combined with serigraphy technique (screen printing). Keywords: war, subject matter, printmaking